Stakeholder Views Regarding Patient Discharge from Intensive Care: Suboptimal Quality and Opportunities for Improvement - Pin Li; Jamie M Boyd; William A Ghali; Henry T Stelfox (Canadian Respiratory Journal)
OBJECTIVE: To provide the first description of intensive care unit (ICU) discharge practices from the perspective of Canadian ICU administrators, and ICU providers from Canada, the United States and the United Kingdom.